PERTUMBUHAN SEMAI BAKAU HITAM (Rhizophora mucronata) PADA BERBAGAI TINGKAT PEMOTONGAN PROPAGUL - Safruni Safruni; M. Mardhiansyah; Evi Sribudiani Sribudiani (JURNAL ILMU-ILMU KEHUTANAN, 2019)
Rhizophora mucronata is mangrove that has called propagul fruit type. The part that extends to propagul (hypokotil) served is as a food reserve while the Propagul germinate and become seedlings. The type of vivipari propagul is propagul which has germinated before falling from the tree. The Rhizophoraceae propagul has germinated in the fruit, bugles and expands from the fruit when the fruit is still above the mother tree. The purpose of this study was to determine the success rate at nurseries and the best cutting rate of propagul. This research was carried out with a completely randomized design method (CRD) with 4 treatments that is; (P0) without propagul, (P1) propagul cutting 25%, (P2) propagul cutting 50%, (P3) propagul cutting 75%, with triplicate each experiment consisting of 10 plants, with the total of 120 units of plants used. Based on the results of the research, propagul cutting did not affect the success nursery rate by showing the yield of 100% seedlings, the best propagul cutting presentage is 25% with a growth rate of 6.91 cm.